Improvisasi media pembelajaran pendidikan agama Islam di era modern: Peralihan dari media konvensional ke platform digital - Pramatya, Rafif Danu; Azzahwah, Shofarina; Hunaida, Wiwin Luqna (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2025)
Education plays a vital role in shaping human development. As digital technology rapidly evolves, Islamic Religious Education (IRE) must stay grounded in its spiritual foundations while embracing modern advancements. This shift has transformed learning processes, urging educators to adopt roles beyond mere information delivery. They are now expected to serve as facilitators, guiding students through relevant and value-oriented learning experiences. This research adopts a library-based method using a qualitative-comparative approach to analyze conventional and digital learning media. The objective is to explore how IRE learning tools are being adapted in the digital age and to highlight the significance of these changes in maintaining both educational relevance and Islamic values.